Optimisation of light spectral quality to improve plant growth and development - Smith, Hayley L. (2017)
The many advantages of light-emitting diode (LED) grow lamps in terms of programmability and energy efficiency make them an attractive replacement for old lighting systems. However, when replacing conventional broad-waveband ‘white’ lighting with narrow-waveband LED lighting it is important to ensure that the system is able to produce plants of an equal or higher quality and yield. In order to choose suitable light ‘recipes’, i.e. combinations of wavelengths for optimal plant growth, we must first understand how light quality affects plant growth and development. The following work explores the role of each part of the light spectrum, both in natural sunlight in canopy environments in the field and glasshouse, and in an artificial light environment in controlled environment growth rooms.